2022
DOI: 10.7759/cureus.32854
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Awareness of Their Rights and Responsibilities: A Cross-Sectional Study From Al-Ahsa

Abstract: Introduction Patient rights are an essential part of healthcare practice. In fact, patients are one of the most vulnerable members of society. As a result, improving the rights of patients is considered a priority in medical services. Aim The purpose of this study is to measure the level of patients’ awareness of their rights. Subjects and methods This is a cross-sectional study conducted among patients living in Al-Ahsa, Saudi Arabia. A self-administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Researchers also specifically stated that 11.5% of the 104 questions asked to ChatGPT were answered incorrectly. [34] Golan et al [35] assessed the quality of online content on shock wave therapy for erectile dysfunction, and found that ChatGPT's performance in assessing the quality of text content was inadequate and was not consistent with standards set by human evaluators and reliable tools. [35] Momenaei et al [36] evaluated the relevance and readability of the medical information provided by ChatGPT-4 regarding common vitreoretinal surgeries for retinal detachments (RDs), macular holes (MHs), and epiretinal membranes (ERMs).…”
Section: Readabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers also specifically stated that 11.5% of the 104 questions asked to ChatGPT were answered incorrectly. [34] Golan et al [35] assessed the quality of online content on shock wave therapy for erectile dysfunction, and found that ChatGPT's performance in assessing the quality of text content was inadequate and was not consistent with standards set by human evaluators and reliable tools. [35] Momenaei et al [36] evaluated the relevance and readability of the medical information provided by ChatGPT-4 regarding common vitreoretinal surgeries for retinal detachments (RDs), macular holes (MHs), and epiretinal membranes (ERMs).…”
Section: Readabilitymentioning
confidence: 99%
“…[34] Golan et al [35] assessed the quality of online content on shock wave therapy for erectile dysfunction, and found that ChatGPT's performance in assessing the quality of text content was inadequate and was not consistent with standards set by human evaluators and reliable tools. [35] Momenaei et al [36] evaluated the relevance and readability of the medical information provided by ChatGPT-4 regarding common vitreoretinal surgeries for retinal detachments (RDs), macular holes (MHs), and epiretinal membranes (ERMs). They noted that the mean Flesch Kincaid Grade Level and Flesch Reading Ease Score were 14.1 ± 2.6 and 32.3 ± 10.8 for RD, 14 ± 1.3 and 34.4 ± 7 for MD, 14.8 ± 1.3 and 28.1 ± 7.5 for ERM.…”
Section: Readabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Empowered patients could benefit from higher-quality care, cost-effective treatment options, active participation in treatment planning, shorter hospital stays, minimized harm, and upholding dignity. If patient rights are addressed, it could lead to satisfaction, trust, and better healthcare outcomes [ 3 ]. Strong doctor-patient relationships are key to quality care and are even more important in the age of health literacy.…”
Section: Introductionmentioning
confidence: 99%